Poverty in Ecuador: The effects of growth and inequality (2007-2017) - David Vásquez Corral (Desarrollo y Sociedad, 2022)
The Ecuadorian economy was in constant growth during the period under analysis, making it essential to analyze the effect of this on poverty and inequality. The objective of this research is to study the interrelation between economic growth, inequality, and poverty in Ecuador for the 2007-2017 period. Based on the notion of pro-poor growth, the Poverty Equivalent Growth Rate (PEGR) will be used as an index to analyze the average income growth and how its benefits have been distributed among the poor and non-poor. For the Ecuadorian economy, growth has proven to be strictly pro-poor at national level for the total period; however, for the 2013-2017 period, the evidence shows that, for extreme poverty, growth turned out to be anti-poor.